2015
DOI: 10.9738/intsurg-d-15-00004.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Curcumin on an Animal Intestinal Ischemia/Reperfusion Model for Bacterial Translocation and Inflammatory Response

Abstract: Ischemia/reperfusion (IR) injury of the intestine is a major problem in abdominal pathological condition and is associated with a high morbidity and mortality. The purpose of the study is to investigate the effects of curcumin on the bacterial translocation incidence and inflammatory response in rats submitted to bowel ischemia reperfusion injury. Thirty-two Wistar albino rats with a weight of 200 to 250 g were used in the study. They were randomly divided into 3 groups (n = 10 for each group): sham only opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Even if this was the condition in the present study (not a far relationship), curcumin, primarily used as a rectal enema, could have helped hasten clinical and parasitological recovery. A brief explanation, thus, should include 1) regulation of intestinal barrier functioning (Wang et al 2017;Ghosh et al 2018;Liu & Zhu 2022), 2) beneficial effects via gut microbiota [neutralizing diminished butyric acid-producing bacteria along with elevated richness and diversity] (Zhai et al 2020), 3)anti-apoptotic activity on intestinal epithelial tissue (Loganes et al 2017), 4) reduction of bacterial translocation and cytokine levels (Sözen et al 2015) all by curcumin. It should not be unwise to draw a preliminary suggestion that curcumin interacts with giardia via the aforementioned probable mechanisms, which could also explain the efficacy of this study.…”
Section: Resultsmentioning
confidence: 99%
“…Even if this was the condition in the present study (not a far relationship), curcumin, primarily used as a rectal enema, could have helped hasten clinical and parasitological recovery. A brief explanation, thus, should include 1) regulation of intestinal barrier functioning (Wang et al 2017;Ghosh et al 2018;Liu & Zhu 2022), 2) beneficial effects via gut microbiota [neutralizing diminished butyric acid-producing bacteria along with elevated richness and diversity] (Zhai et al 2020), 3)anti-apoptotic activity on intestinal epithelial tissue (Loganes et al 2017), 4) reduction of bacterial translocation and cytokine levels (Sözen et al 2015) all by curcumin. It should not be unwise to draw a preliminary suggestion that curcumin interacts with giardia via the aforementioned probable mechanisms, which could also explain the efficacy of this study.…”
Section: Resultsmentioning
confidence: 99%
“…An animal study suggested that curcumin may improve IBS symptoms by regulating neuro-transmitters such as serotonin, brain-derived neurotrophic factor, and cAMP response element-binding protein signaling pathways processes in the brain and peripheral intestinal system ( 36 38 ). Another study on albino rats showed that curcumin decreases intestinal motility, which explains its therapeutic effects in different gastrointestinal disorders such as like, abdominal pain and IBS ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…In research conducted by Sözen et al, a significant decrease in the inflammatory cytokines (TNF‐α, IL‐6, IL‐1β, and C‐reactive protein [CRP]) as well as aspartate aminotransferase, alanine aminotransferase, lactate dehydrogenase (LDH), and alkaline phosphatase levels were found after treatment of intestinal I/R rats with curcumin. Administration of a solution containing Escherichia coli by orogastric intubation and further microbiological evaluation of blood and mesenteric lymph nodes cultures revealed significantly fewer positive cases in cultures derived from the curcumin‐treated intestinal I/R group than untreated group (Sözen et al, 2015). In another research, curcumin preconditioning reduced intestinal I/R injury by drastically lowering Chiu's score and β‐hexosaminidase level and downregulating tryptase expression in the intestinal tissues is linked to suppressed mast cell activation in the rat (Zhao et al, 2014).…”
Section: Introduction To Ischemia–reperfusion Injurymentioning
confidence: 99%